Official regularization of settlement names on the territory of present-day Transcarpathia in the era of the First Czechoslovak Republic (1919–1938) - Dobos Sándor; Олександр Добош; Oleksandr Dobosh („RIK-U” Kft., 2018)
Abstract. During the 20th century several territorial and governmental changes occurred in the Carpathian Basin that caused several regularizations of settlement names by the authorities in the territory of present-day Transcarpathia – especially because of political and ideological purposes, without taking cultural traditions, historical backgrounds into consideration.
https://kmf.uz.ua/wp-content/uploads/2018/11/Multicult-Diversity_Book-of-Abstracts_23-10-2018.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00006453
Keywords: First Czechoslovak Republic; 1919-1938; Transcarpathia; settlement names